2017
DOI: 10.4103/1008-682x.173444
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion status, Gleason score and number of positive cores in biopsy pathology are predictors of positive surgical margin following laparoscopic radical prostatectomy

Abstract: This study was designed to define possible preoperative predictors of positive surgical margin after laparoscopic radical prostatectomy. We retrospectively analyzed the records of 296 patients with prostate cancer diagnosed by prostate biopsy, and eventually treated with laparoscopic radical prostatectomy. The prognostic impact of age, prostate volume, preoperative prostate-specific antigen, biopsy Gleason score, maximum percentage tumor per core, number of positive cores, biopsy perineural invasion, capsule i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…In the meta-analysis conducted by Novara et al , [16] the mean PSM rate was 15%. However, Xu et al [24] and Yang et al [25] reported PSM rates of 44.2% and 29.1% in the Chinese population, which were comparable to our study. There are several possible reasons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the meta-analysis conducted by Novara et al , [16] the mean PSM rate was 15%. However, Xu et al [24] and Yang et al [25] reported PSM rates of 44.2% and 29.1% in the Chinese population, which were comparable to our study. There are several possible reasons.…”
Section: Discussionsupporting
confidence: 90%
“…Tuliao et al 's study [20] suggested that the number of preoperative positive biopsy cores was a predictor of PSM. Yang et al [25] reported that PSM was more common in patients with a more positive core number and bilateral positive cores.…”
Section: Discussionmentioning
confidence: 99%
“…It was worth noting that the higher risks of PSMs noted in patients with small prostates were correlated with tumour volume (TV), grade and extraprostatic extension (EPE) (Hong, Poon, Sjoberg, Scardino, & Eastham, 2014;Yadav et al, 2009;Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The dose-response analysis between prostate weight and the risk of positive surgical margins pathologic characteristics by conducting a comparison of men with PW of ≥100 g and of <20 g, and indicated that older men with larger PW were more likely to have lower risks of seminal vesicle invasion than younger counterparts. Several studies found that greater biopsy Gleason scores and prostate-specific antigen (PSA) level both had positive associations with PSMs (Liss, Osann, & Ornstein, 2008;Yang et al, 2017). Nevertheless, there was a controversy in leadtime bias that patients with larger prostates had their cancers detected early based on biopsy PSA level, most probably due to an enlarged prostate gland (Foley et al, 2003).…”
Section: F I G U R Ementioning
confidence: 99%
“…Journal of Nephropathology, Vol 8, No 4, October 2019 www.nephropathol.com 2 the invasion has been found to be in relation with PSA levels (2,9,10).…”
Section: Original Articlementioning
confidence: 98%